Clinical, laboratory and histopathologica investigation of the protective effect of dimethylsulfoxide (dmso) on experimentally induced various types of intestinal strangulation obstruction in dogs - Cengiz Ceylan; Yılmaz Koç (Eurasian Journal of Veterinary Sciences)
The aim of this study ıs lo evaluate the protective effect of dimethylsulfoxide (DMSO), a scavenger of hydroxyl radical, on the experimentally induced ischemia reperfusion injury by two different intestinal strangulation obstruction in dogs. A total of 24 dogs were used and divided into 4 groups, each group having 6 dogs. The dogs in groups 1 and 2 were subjected to 1 hour ol no flow ischemia and 1 hour of reperfusion, and then, for Ihe treatment ol animals at the beginning of reperfusion, group 1 was treated with 0.9% NaCI 15 ml/kg), and the Olher with 20% DMSO (1 g/kg) The dogs in groups 3 and 4 were subjected lo 24 hours of low How ischemia and t hour ot reperfusion, and then, tor Ihe treatment of animals at the beginning of reperfusion. group 3 was treaied with 0.9% NaCI (5 ml/kg), and Ihe other wilh 20% DMSO (1 g/kg) To carry out no flow (aperfusion) ischemia the jeiunal artery and vein of the distal jejunum close to ileum were clamped completely wilh Bulldog clamps in groups 1 and 2. To carry out the low flow ischemia (hipoperfusion) the vessels mentioned above were iigated to decrease blood flow about 50% in groups 3 and 4 The distal jejunal segment was also ligated with Penrose drains in its proximal and distal ends 20-30 cm apart tor luminal occlusion in all animals. Blood, peritoneal fluid and intestinal biopsy samples were collected both before ischemia and after ischemia and reperfusion. Complete blood count, oxygen status, acid-base, electrolyte and glucose levels in blood were measured, and lactic acid level in peritoneal fluid was also measured. Moreover, intestinal mucosal damage was also determined based on Chiu's standard scale. One hour after reperfusion, statistically significant improvements were observed (P<0,05) on pH. PC02, P02, 02 saluration and lactic acid level in animals treated wilh DMSO in comparison with NaCI treated animals. It was concluded that DMSO provided an incomplete healing, and that use of DMSO itself could not be sufficient on the ischemia reperfusion injury in the intestines.